Managing Retention in ODL Institutions: A Case Study on Open University Malaysia and Sukhothai Thammathirat Open University - Latifah Abdol Latif; Sumalee , Sungsri; Ramli Bahroom, (Open University Malaysia (OUM), 2009)
Retaining learners has always been an ongoing challenge for open and distance learning (ODL) institutions worldwide. There is no exception for Open University Malaysia (OUM) and Sukhothai Thammathirat Open University (STOU). In both institutions, it was found that the attrition rate is highest in the early part of a learner’s study programme. This represents a huge loss in revenue for the institutions and a lost opportunity for learners in terms of enhancing their level of personal and career development. Both OUM and STOU have undertaken various interventions to mitigate early attrition. This paper reviews the major retention initiatives at both institutions so that they can learn from each other’s experiences. The reasons for learner drop-outs as well as the interventions at both institutions are found to be quite similar. Despite differences in size and age, the two institutions believe they should collaborate in order to further enhance the effectiveness of their retention efforts. Several issues and challenges peculiar to each institution were identified to determine the best areas in which both institutions could collaborate in. (Authors' abstract)